Functional outcome of tongue motions with selective hypoglossal nerve stimulation in patients with obstructive sleep apnea - Heiser, Clemens; Maurer, Joachim T.; Steffen, Armin (Sleep and breathing, 2016)
Background: Selective upper airway stimulation of the hypoglossal nerve is a novel therapy option for obstructive sleep apnea. Different tongue motions were observed after surgery during active therapy. Methods: We examined tongue motions in 14 patients (mean age 51 ± 10 years) who received an implantation of an upper airway stimulation system (Inspire Medical Systems) from September 2013 to February 2014 in three different implantation centers in Germany after surgery. Sleep recording was performed preoperatively: 2 months (M02) and 6 months (M06) after surgery. Results: There were three different tongue motions observed after surgery at 1 month (M01), M02, and M06 after surgery: bilateral protrusion (BP), right protrusion (RP), and mixed activation (MA). At M01: 10 BP, 2 RP, and 2 MA; at M02: 12 BP, 0 RP, and 2 MA; and at M06: 12 BP, 0 RP, and 2 MA could be detected. The average apnea-hypopnea index (AHI) was reduced from 32.5 ± 14.2/h before surgery to 17.9 ± 23.3/h at M02 and 14.1 ± 19.8/h at M06. An increased reduction in AHI was found in BP and RP group (Baseline: 29.6 ± 12.6/h; M02: 12.06 ± 14.1/h; M06: 9.7 ± 12.6/h) compared to the MA group (Baseline 49.6 ± 13.8/h; M02: 49.7 ± 5.1/h; M06: 40.5 ± 4.1/h). Conclusions: These findings suggest that the postoperative tongue motions in upper airway stimulation are associated with the therapy outcome. The stimulation electrode placement on the hypoglossal nerve for selective muscle recruitment may play a role in the mechanism of action.
Gesehen am 07.05.2019
Published online: 28 August 2015